Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài

Những câu hỏi liên quan
Ân Trần
Xem chi tiết
Minh Triều
9 tháng 7 2015 lúc 10:49

a) -7x2 + 5xy +12y2

=-7x2-7xy+12xy+12y2

=-7x(x+y)+12y(x+y)

=(x+y)(12y-7x)

b) x8 + 3x4 + 4

=x8+4x4+4-x4

=(x4+2)2-x4

=(x4-x2+2)(x4+x2+2)

=(x4+x2-2x2+2)(x4+x2+2)

=[x2(x+1)-2(x+1)](x4+x2+1)

=(x+1)(x2-2)(x4+x2+1)

Không Tên
2 tháng 11 2018 lúc 19:25

\(x^8+3x^4+4\)

\(=x^8+4x^4+4-x^4\)

\(=\left(x^4+2\right)^2-x^4\)

\(=\left(x^4+x^2+2\right)\left(x^4-x^2+2\right)\)

Không Tên
2 tháng 11 2018 lúc 19:37

\(x^8+3x^4+4\)

\(=x^8+4x^4+4-x^4\)

\(=\left(x^4+2\right)^2-x^4\)

\(=\left(x^4+x^2+2\right)\left(x^4-x^2+2\right)\)

Nguyenngocdiem
Xem chi tiết
Nguyễn Lê Phước Thịnh
11 tháng 7 2023 lúc 8:48

13: =x(a^3-1)-b(a-1)

=x(a-1)(a^2+a+1)-b(a-1)

=(a-1)(a^2x+a*x+x-b)

12: =(x-y)(x+y)-(x-y)

=(x-y)(x+y-1)

10: =3(x^2-4y^2)

=3(x-2y)*(x+2y)

7: =x^2-x-5x+5=(x-1)(x-5)

8: =x^2+3x+4x+12=(x+3)(x+4)

9: =2x^2-6x-x+3=(x-3)(2x-1)

Xin chào
Xem chi tiết
ILoveMath
22 tháng 11 2021 lúc 20:25

\(y^2-12y+36-144x^2=\left(y-6\right)^2-\left(12x\right)^2=\left(y-12x-6\right)\left(y+12x-6\right)\)

Lấp La Lấp Lánh
22 tháng 11 2021 lúc 20:25

\(=\left(y^2-12y+36\right)-144x^2=\left(y-6\right)^2-144x^2=\left(y-12x-6\right)\left(y+12x-6\right)\)

Thuy Bui
22 tháng 11 2021 lúc 20:25

\(( y − 12 x − 6 ) ( y + 12 x − 6 )\)

Mai Thúy Hiền
Xem chi tiết
Quynh Nhu
Xem chi tiết
Lấp La Lấp Lánh
13 tháng 10 2021 lúc 20:22

\(12y-9x^2+36-3x^2y\)

\(=\left(36-9x^2\right)-\left(3x^2y-12y\right)\)

\(=-9\left(x^2-4\right)-3y\left(x^2-4\right)\)

\(=\left(-3\right)\left(x-2\right)\left(x+2\right)\left(3+y\right)\)

 

Minh Hiếu
13 tháng 10 2021 lúc 20:24

\(12y-9x^2+36-3x^2y\)

\(=\left(12y-3x^2y\right)-\left(9x^2-36\right)\)

\(=3y\left(4-x^2\right)-9\left(x^2-4\right)\)

\(=3y\left(4-x^2\right)+9\left(4-x^2\right)\)

\(=\left(3y+9\right)\left(4-x^2\right)\)

\(=3\left(y+3\right)\left[\left(2^2\right)-x^2\right]\)

\(=3\left(y+3\right)\left(2+x\right)\left(2-x\right)\)

Nguyễn Thanh Bình
13 tháng 10 2021 lúc 20:25

=(−3)(x−2)(x+2)(3+y)

Phạm Thị Anh Thi
Xem chi tiết
võ dương thu hà
Xem chi tiết
Rhider
Xem chi tiết
︵✰Ah
11 tháng 1 2022 lúc 17:43

 

5 x2 - 5xy+2x−2y = 2x ( x - y) + 2( x - y) = 2( x + 1)( x - y)

Thảo Nguyên Xanh
Xem chi tiết
Trà My
9 tháng 7 2017 lúc 23:45

\(=\left(12x^2-18xy+9x\right)+\left(8xy-12y^2+6y\right)-\left(4x-6y+3\right)\)

\(=3x\left(4x-6y+3\right)+2y\left(4x-6y+3\right)-\left(4x-6y+3\right)\)

\(=\left(4x-6y+3\right)\left(3x+2y-1\right)\)